An unusual presentation of gastrointestinal obstruction in a three-year-old boy - Boybeyi, Ozlem; Ciftçi, Arbay Ozden; Topaloğlu, Haluk (The Turkish Journal of Pediatrics, 2009)
We report a case presenting with severe intermittent intestinal obstruction, most probably due to enteric nervous system abnormality associated with megacystis and micturition difficulty. Medical treatment consisting of pyridostigmine was very successful in our patient. The clinicopathologic features of this very rare entity and its medical treatment are discussed with a brief review of the etiopathogenesis.